2009
DOI: 10.1016/j.jvs.2009.01.007
|View full text |Cite
|
Sign up to set email alerts
|

The role of the vascular surgeon in anterior retroperitoneal spine exposure: Preservation of open surgical training

Abstract: Vascular expertise is important in anterior retroperitoneal lumbar spine exposure. Minor venous injuries frequently occur during exposure and instrumentation. Significant vascular injuries, while rare, occur during instrumentation, therefore the vascular surgeon should remain present throughout the entire procedure. The vascular manipulations required during exposure of the L4-5 disc offer an excellent opportunity for open vascular surgical experience. Vascular surgeon involvement in these cases allows for pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
80
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(92 citation statements)
references
References 8 publications
5
80
0
4
Order By: Relevance
“…They found 11 % incidence of major and 24 % incidence of minor complications. Chiriano et al [32] found the incidence of minor Numerals refer to number of patients vascular injuries (requiring repair) to be 24 %, while the incidence of serious vascular injury was 3 %. Jarrett et al [33] reported that even the use of an expert ''access surgeon'' for anterior trans-lumbar approach did not reduce the incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found 11 % incidence of major and 24 % incidence of minor complications. Chiriano et al [32] found the incidence of minor Numerals refer to number of patients vascular injuries (requiring repair) to be 24 %, while the incidence of serious vascular injury was 3 %. Jarrett et al [33] reported that even the use of an expert ''access surgeon'' for anterior trans-lumbar approach did not reduce the incidence of complications.…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of diseased anterior column, laminectomy is said to aggravate the spinal instability [32,33]. Stability of the vertebral column following posterior decompression is no longer a major concern following the advent of contemporary posterior segmental spinal instrumentation systems.…”
Section: Discussionmentioning
confidence: 99%
“…3,7,10,11 Because of advances in surgical techniques and surgeon comfort, thoracolumbar corpectomies are increasingly performed via a posterior approach. 1,8,9,12,13,16 In our study, we found similar morbidity for the anterior-only and transpedicular approaches with regard to complication rate, EBL, and operative time.…”
Section: Discussionmentioning
confidence: 99%
“…Brau et al [3] also use CT to assess the inflammation around the vessels and predict difficult dissection. Experienced access surgeons should be consulted [13,24], especially if local conditions are not satisfactory (major adhesions, sepsis, L4-L5 or L5-S1 level, surgery at the same spinal level, necessity of implant removal). In our series, an orthopedic surgeon performed all the approaches, but a vascular surgeon had to perform the three vascular repairs.…”
Section: Discussionmentioning
confidence: 99%